Political issues in contemporary art of Ukraine - Usenko, Natalia (Journal of Education Culture and Society, 2020)
At the beginning of the XXI century Ukrainian art observed activization of the artist’s interest for the political life of the country. The starting point was 2004, marked by protests against unfair elections in the country, the birth of the first “Maidan” and “Orange revolution”. In a number of artistic actions organized by art groups we can see the reflection of the revolution events and, later, the frustrations of its ideals. The most striking manifestation of political issues in contemporary art in Ukraine was the great creativity following the second “Maidan” (2013). In this spontaneous Performance everyone plays a role: the participants are the protesters, official persons, fighters of “Berkut” and interior force troops, journalists and others. Protesters’ tents, barricades, a statue of Lenin and “Maidan” itself (or Independence Square) as a place of free will and creativity became the Symbols of the “Maidan” and its own art objects.